Contraception in perimenopause - Soltes, Barbara A (Menopause (New York, N.Y.), 2025)
Perimenopause is characterized by wide hormone fluctuations and irregular menstrual cycles for 5 or more years preceding menopause and lasts until 12 months of amenorrhea have been achieved. It represents a period of reproductive transition with a decline in fertility. However, unintended pregnancies do occur, with a high risk for poor outcomes and maternal complications. All women transitioning through perimenopause should be adequately counseled. There are many hormone and nonhormone contraceptive methods that are highly effective and suited to the personal and medical needs of the perimenopausal woman. Contraception should continue until menopause is confirmed.